Mental preparation in runners: gender differences, competition levels, and psychological training effects on performance - Kelemen, Bence; Tóth, Renátó; Benczenleitner, Ottó; Tóth, László (Frontiers in Sports and Active Living, 2024)
The present study aimed to investigate the mental and sports psychological preparation, as well as tactical preparation, of distance runners for competition. We examined whether there are differences based on gender, competition level and various race disciplines, as well as how mental preparation influences sports skills applicable in different competitive situations. The sample consisted of 201 distance runners who completed the Sports Mental Training Questionnaire (SMTQ) alongside assessments of their sports psychology and race tactics. The results indicated that neither gender, competition level, nor race discipline had a significant impact on mental preparedness. However, women demonstrated notably higher scores in the use of self-talk as a mental technique. Additionally, participants who received training in sports psychology scored significantly higher across several mental skills, as well as on the overall mental preparedness score. This article validates the SMTQ and its association with mental readiness, as confirmatory factor analysis demonstrates adequate validity. Additionally, mental preparation was found to enhance performance and well-being among distance runners. Further research is needed to explore the impact of group interventions to broaden the reach of mental training programs.